DiabetologNytt (1996–1999) - Språkbanken Text (University of Gothenburg, 2024)
The paper DiabetologNytt (Diabetologynews) 1996-1999

Tidningen DiabetologNytt 1996-1999
DiabetologNytt (1996–1999)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik